Morality Tale or Attempt at Reportage? Yet Another Look at Peter von Dusburg’s Description of the Prussian Pagan Religion - Rasa Mažeika (Acta Historica Universitatis Klaipedensis, 2023)
The story by the Teutonic Order chronicler Peter von Dusburg about the Prussian pagan priest Criwe and his sanctuary Romowe has for centuries provoked historiographical arguments about the nature of the Baltic pagan religion and the interpretation of Medieval chronicle sources relating to the Balts. This article focuses on an interpretation of Dusburg’s text, without attempting to decide on the reality of ancient pagan religious practice. Through a ‘close reading’ approach to actual words and the contexts of sentences that are often extracted and used out of context, the article argues against either dismissing the passage as an invented moral exemplum or accepting it literally. A speculative explanation for Dusburg’s portrayal of the pagan priest Criwe as a pope is presented for consideration. Moreover, through a reminder of the often-neglected context of the Criwe passage in book III of the chronicle, this article suggests an overarching aim for Dusburg’s portrayal of the Old Prussians, which is not as the ‘avatar of evil’ often proposed in historiography, but rather as simple peoples who should be left to the Teutonic Order and not to the Franciscans favoured at that time by Grand Duke Gediminas of Lithuania. To aid readers, the article contains the whole Latin passage (rather than the extracts often quoted), and an English translation by Rasa Mažeika.